Magnetic Characterization of Sand and Boulder Samples from Citarum River and Their Origin - Sudarningsih Sudarningsih; Luki Maulana; Satria Bijaksana; Abd Hafidz; Aditya Pratama; Widodo Widodo; Irwan Iskandar (Journal of Mathematical and Fundamental Sciences, 2017)
The Citarum River is a nationally strategic river located near Bandung, the capital city of West Java Province. The feasibility of using magnetic methods for monitoring pollution level is currently being tested in the river. Due to its location in a volcanic area, the sediments from the river are expected to be highly magnetic. In this study, sand and boulder samples from Balekambang, a relatively pristine upstream area of the river, were subjected to magnetic and geochemical characterizations to establish the baseline for unpolluted sediments. Such baseline is important for future magnetic monitoring of sediments in the river. The mass-specific magnetic susceptibility of boulder samples was found to be varied from 819.2 to 2340.5 Ã— 10-8m3 kg-1 while that of sand samples varied from 2293.9 to 3845.3 Ã— 10-8m3 kg-1. These high magnetic susceptibility values infer that river sediments are highly magnetic even before being contaminated by industrial and household wastes. The predominant magnetic mineral in sand samples was multi-domain magnetite while that in boulder samples was single to pseudo-single domain magnetite. These differences were supported by the results from petrographic and XRF analyses, implying that the sand and boulder samples originated from different geological formations.